Healthcare professionals and stem cell research: Challenges in years of 2024 - Subrata, Sumarno Adi (Universitas Muhammadiyah Magelang, 2023)
In the ever-evolving healthcare landscape, professionals find themselves at the intersection of cutting-edge science and transformative innovation. This is more evident than stem cell research and its applications in medical practice. Let us embark on a narrative journey, exploring the role of healthcare professionals in the dynamic world of stem cell innovation. As the narrative unfolds, we find ourselves in a research laboratory where healthcare professionals with backgrounds in molecular biology, genetics, and regenerative medicine collaborate to unlock the secrets held within the microscopic world of stem cells. These professionals, armed with curiosity and a commitment to advancing medical science, delve into the complexities of cellular regeneration. Keywords: Innovation in stem cell; technology development; healthcare services; quality of care; future of health services